H. Bauerlund, Samfundsfaglig bibliografi, samfundsfagsnyt, 1977, 444 s. Kr. 60,00 (-1- forsendelse). Fås ved bestilling til samfundsfagsnyt, agsnyt, v/H.C. Bauerlund, Esberns Allé BA, 2860 Søborg - Elklit:, Jørgen (Politica, 1977)
-